Focal organizing pneumonia simulating lung malignancy: treated with prednisolone - Hemanth Kilaru; Mohd Vaseem Jalna; Satish Chandra Kilaru; Eshwar Chandra Nandury; Mohammed Zia Ur Rehman Khan (Respirology Case Reports, 2019)
Focal cryptogenic organizing pneumonia (FOP) is a localized form of cryptogenic organizing pneumonia (COP). It is an uncommon clinicopathological entity associated with non‐specific symptoms and radiographic findings simulating lung malignancy. Incidence of idiopathic FOP is not known and only reported as case series. Its treatment usually involved surgical resection. Here, we report a case of a 62‐year‐old female presenting with a history of dyspnoea, persistent paroxysms of dry cough, and low‐grade fever of three weeks duration with a solitary consolidation on imaging. Computed tomography‐guided biopsy showed an organizing pneumonia pattern. A therapeutic trial with prednisolone resulted in resolution without the need for surgical resection, without recurrence after follow‐up for 12 months.